2023
DOI: 10.1039/d2ra06669f
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of polydopamine sphere synthesis using TRIS: relationship between synthesis conditions and final properties

Abstract: Synthesized PDA shows unexpected regular structure giving crystallinity. Kinetic parameters for spherical PDA are reported showing that polymerization depends upon TRIS concentration and temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…The thermal profile of pDA similarly presents four thermal events, and the overall behavior verifies the successful polymerization from DA. The first weight loss (25–100 °C) is attributed to the evaporation of weakly bound water due to high pDA hygroscopicity . The second weight loss (100–240 °C) proves the presence of intramolecular, strongly bonded water trapped after polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal profile of pDA similarly presents four thermal events, and the overall behavior verifies the successful polymerization from DA. The first weight loss (25–100 °C) is attributed to the evaporation of weakly bound water due to high pDA hygroscopicity . The second weight loss (100–240 °C) proves the presence of intramolecular, strongly bonded water trapped after polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…However, in our study, BC hydrogel showed an absorption peak at 260 nm, presumed to have come from the adherence of bacterial proteins or bacterial media components. The maximum absorbance of dopamine monomer lies at 280 nm [ 24 ]. On the other hand, BC/PDA-150 and BC/PDA-300 hydrogels containing polydopamine (PDA) change the biomaterial’s optical properties.…”
Section: Resultsmentioning
confidence: 99%
“…PDA NPs were prepared through self-polymerization of dopamine in Tris-buffer (pH 8.5). 34 The obtained spherical NPs had an average hydrodynamic radius of 158.4 AE 39.2 nm and the characteristic negative surface potential (À29.2 AE 1.9 mV), owing to the abundant presence of imine and quinone moieties within the PDA backbone. 35,36 To obtain positively charged carriers and facilitate nucleic acid binding, PDA NPs were incubated with poly-L-arginine (pArg, M w = 5-15 kDa) under mild basic conditions (10 mM NH 4 OH, aq.)…”
Section: Nanoscale Horizonsmentioning
confidence: 99%